Auf dem Weg zum Kunden. Die Deutsche Rentenversicherung vereinfacht ihre Bescheide und Formulare - Fiedler-Rauer, Heiko; Margies, Burkhard (ZERL - Zeitschrift für Europäische Rechtslinguistik, 2021)
The notices of Deutsche Rentenversicherung are changing their face. In order to ensure that everybody insured as well as pensioners can better understand the decisions of Deutsche Rentenversicherung, the notices are becoming more comprehensible, clearer and more personal. The article, originally a poster presentation, describes the journey of an interdisciplinary team of Deutsche Rentenversicherung and the most important milestones along the way.